2016
DOI: 10.1186/s13195-016-0180-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation as a memory enhancer in patients with Alzheimer’s disease: a randomized, placebo-controlled trial

Abstract: BackgroundThe purpose of this study was to assess the efficacy of transcranial direct current stimulation (tDCS) on verbal memory function in patients with Alzheimer’s disease.MethodsWe conducted a randomized, placebo-controlled clinical trial in which tDCS was applied in six 30-minute sessions for 10 days. tDCS was delivered to the left temporal cortex with 2-mA intensity. A total of 25 patients with Alzheimer’s disease were enrolled in the study. All of the patients were diagnosed according to National Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
112
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 34 publications
3
112
0
2
Order By: Relevance
“…For studies with AD patients, roughly half of studies employed tDCS as the stimulation tool [81-87], the other using TMS [88-94]. Moreover, the majority of the studies have focused on memory, the core clinical symptom.…”
Section: Nibs and Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…For studies with AD patients, roughly half of studies employed tDCS as the stimulation tool [81-87], the other using TMS [88-94]. Moreover, the majority of the studies have focused on memory, the core clinical symptom.…”
Section: Nibs and Dementiamentioning
confidence: 99%
“…Moreover, the majority of the studies have focused on memory, the core clinical symptom. Ten studies were designed as multiple session paradigm [81, 83, 84, 86-88, 90, 92-94], and a cognitive training was combined with the stimulation protocol in 3 of the brain stimulation studies on AD [84, 93, 94]. …”
Section: Nibs and Dementiamentioning
confidence: 99%
“…In this study, both anodal and cathodal stimulation showed a change in cognitive function improvement and shortening of P300 latency. However, in other randomized parallelgroup clinical trials, tDCS stimulation did not show significant effects on enhancement of cognitive function [76][77][78] (Table 1). Most of these previous clinical studies were small, and the characteristics of subjects, conditions of stimuli and outcome measures were different from study to study.…”
Section: Clinical Trials Of Tdcs In Patients With Admentioning
confidence: 85%
“…Seven double-blind RCTs have been so far conducted for AD [20][21][22][23][24][25][26] . Here we review five of them that evaluated multiple-session effects 20,22,23,25,26 since a meta-analysis suggests that a larger number of sessions may be more effective 27 .…”
mentioning
confidence: 99%
“…Here we review five of them that evaluated multiple-session effects 20,22,23,25,26 since a meta-analysis suggests that a larger number of sessions may be more effective 27 . Two of five controlled trials revealed significant effect on some domains in AD.…”
mentioning
confidence: 99%